Myxopapillary ependymoma as a cause of back pain in a young male – A case report - Ngo, Trung P (Canadian Chiropractic Association, 2013)
OBJECTIVE: Primary spinal cord tumours are rare causes of low back pain but can be a significant cause of morbidity if undiagnosed and untreated. The following is a case of a young male patient presenting with low back pain and radicular symptoms caused by myxopapillary ependymoma. CLINICAL FEATURES: A nineteen year old male presented to an orthopaedic surgeon with a long history of back pain. He was initially diagnosed with soft tissue injuries and discharged. He began to experience erectile and bowel dysfunction two years later and was re-referred to the orthopaedic surgeon by his family physician but was lost to follow-up. The patient did not present to the surgeon until two years after his symptom profile changed. At that point, MRI examinations revealed a large myxopapillary ependymoma extending from T12 to L4 that was confirmed by a pathologist. INTERVENTION AND OUTCOME: The tumour was surgically resected with subsequent adjuvant radiotherapy. After one year, the patient required continued catheterization and had poor anal tone. His back and leg complaints were almost normal. Follow-up MRI examinations revealed no disease progression or new spinal lesions at 4 years after the initial diagnosis. CONCLUSION: The clinical presentation of primary spinal cord tumours is non-specific and can easily be missed. In cases of chronic back pain, signs and symptoms should be regularly monitored for changes indicative of progressive neurological compromise such as sensory, motor and bowel/bladder dysfunction. If there is deterioration of clinical signs and symptoms, a spinal tumour should be considered in the list of differential diagnoses. Delayed diagnosis and treatment of these rare causes of back pain could lead to poor outcomes; therefore, a referral to a surgeon should be done immediately with proper follow up to ensure continuity of care.